THE IMPACT OF SOCIAL STIGMA AND LOSS OF FACE ON MENTAL HEALTH HELP-SEEKING BEHAVIOR AMONG UNIVERSITY STUDENTS IN MALAYSIA: EXAMINING MEDIATING RELATIONSHIPS - Ye Qian Loong; Siew Tin Tan; Sun Wei Yeoh; Cheng Sim Katherine Poh; Afiqah Yeop; Qi Rui Goh; Meng Chuan Ho, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Students in higher education often experience mental and emotional barriers. While this population is susceptible to mental health issues, university students in particular face social stigmatization of mental health by their peers and concerns about losing face, which are significant barriers to accessing mental health services. This is particularly important for Malaysian students, who espouse Asian cultural values and are more sensitivity to social status and reputation. Therefore, the study aims to examine the mediating role of loss of face on perceived social stigma and help-seeking behavior among Malaysian university students. The research participants are 306 university students aged 18 and above in Malaysian context, and this cross-sectional design study will be enlisted through convenience sampling. The results obtained from multiple linear regression indicated perceived social stigma negatively predicted the help-seeking behavior (β = -0.26, p < .001). Moreover, loss of face also negatively predicted help-seeking behavior (β = -0.36, p < .001). As hypothesized, loss of face was found to have a statistically significant mediating effect (indirect effect = -0.13, p < 0.01) on the relationship between perceived social stigma and help-seeking behavior, accounting for approximately 33% of the total effect. This study contributes new statistical insights to the field of mental health, addressing existing gaps in knowledge and providing valuable reference material for the development of mental health awareness campaigns aimed at improving attitudes towards help-seeking among the public.